Extent of the rain‐snow transition zone in the western U.S. under historic and projected climate. Issue 13 (1st July 2014) - Klos, P. Zion; Link, Timothy E.; Abatzoglou, John T.
Abstract This study investigates the extent of the rain‐snow transition zone across the complex terrain of the western United States for both late 20th century climate and projected changes in climate by the mid‐21st century. Observed and projected temperature and precipitation data at 4 km resolution were used with an empirical probabilistic precipitation phase model to estimate and map the likelihood of snow versus rain occurrence. This approach identifies areas most likely to undergo precipitation phase change over the next half century. At broad scales, these projections indicate an average 30% decrease in areal extent of winter wet‐day temperatures conducive to snowfall over the western United States. At higher resolution scales, this approach identifies existing and potential experimental sites best suited for research investigating the mechanisms linking precipitation phase change to a broad array of processes, such as shifts in rain‐on‐snow flood risk, timing of water resource availability, and ecosystem dynamics.